G.U Pope's English Translation of Thirukural - Batumalai, Gomathi; Mani, Manimangai; Veeraputhran, Veeramohan (University of Malaya, 2023)
Thirukural is one of the most popular Tamil literary works to date. Thiruvalluvars Thirukural, also known as Ulagapothumarai, Poiyamozhi, Muppaal, and so on, is widely used by people worldwide. Thirukural showcases life concepts and has been translated into more than 40 languages partially and wholly by more than 60 scholars. These translations have delivered Thirukural to the entire world. This study is about G.U. Popes English translation of Thirukural. The eminent British scholar and linguist G.U. Pope, abbreviated from George Uglow Pope, made substantial contributions to Tamil literature and culture. The English translation of the Thirukural, a masterwork of Tamil literature credited to the ancient poet Thiruvalluvar, is one of his most illustrious works. This study mainly identifies and analyses the strength and weaknesses of G.U.Popes translation of Thirukural. Data has been collected and textually analysed using Newmark Translation Theory (1988). This analysis found that the English translation of Thirukural by G.U. Pope is mostly accurate, with few inaccuracies in certain components. Thus, an accurate translation of literature from a source text to a targeted language brings the beauty and message of the literature to the audience.